2017
DOI: 10.5194/hess-21-4053-2017
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the influence of snow surface processes on soil moisture dynamics and streamflow generation in an alpine catchment

Abstract: Abstract. The assessment of flood risks in alpine, snowcovered catchments requires an understanding of the linkage between the snow cover, soil and discharge in the stream network. Here, we apply the comprehensive, distributed model Alpine3D to investigate the role of soil moisture in the predisposition of the Dischma catchment in Switzerland to high flows from rainfall and snowmelt. The recently updated soil module of the physics-based multilayer snow cover model SNOWPACK, which solves the surface energy and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 61 publications
(84 reference statements)
0
25
0
Order By: Relevance
“…As data retrieval methods improve and higher resolution products become available (Bühler, Adams, Bosch, & Stoffel, 2016;Nolan, Larsen, & Sturm, 2015;Painter et al, 2016), modelling efforts will similarly increase in resolution (Brauchli, Trujillo, Huwald, & Lehning, 2017;Hedrick et al, 2018). Hydrologic models often assume snowmelt infiltrates vertically into the soil through one-dimensional intra-snowpack percolation occurring uniformly across a grid cell or lumped hydrologic response unit (e.g., Kormos et al, 2014;Wever, Comola, Bavay, & Lehning, 2017). In order to obtain physically realistic results from these models, it is necessary to understand the nature of intra-snowpack flow paths and the resulting meltwater outflow variability (Webb, Williams, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As data retrieval methods improve and higher resolution products become available (Bühler, Adams, Bosch, & Stoffel, 2016;Nolan, Larsen, & Sturm, 2015;Painter et al, 2016), modelling efforts will similarly increase in resolution (Brauchli, Trujillo, Huwald, & Lehning, 2017;Hedrick et al, 2018). Hydrologic models often assume snowmelt infiltrates vertically into the soil through one-dimensional intra-snowpack percolation occurring uniformly across a grid cell or lumped hydrologic response unit (e.g., Kormos et al, 2014;Wever, Comola, Bavay, & Lehning, 2017). In order to obtain physically realistic results from these models, it is necessary to understand the nature of intra-snowpack flow paths and the resulting meltwater outflow variability (Webb, Williams, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the sparse availability of spatially distributed measurements of LWC, snowmelt runoff and SWE — especially over large areas such as the catchments investigated in this study — such a direct validation of the model results seems unfortunately impossible. Yet the SNOWPACK model has been validated extensively in the past, including point‐scale simulations (Schmucki et al, ; Wever, Jonas, et al, ), focussing on the water transport scheme within the model (Wever et al, ; Wever, Fierz, et al, ; Würzer et al, ), and by distributed simulations using MeteoIO (Lehning et al, ; Schlögl, Marty, Bavay, & Lehning, ; Wever et al, ). Schlögl et al () conducted a sensitivity analysis to systematically investigate the impact of different model setups on the robustness of modelled SWE and found that the input uncertainties of distributed simulations are in the same range as uncertainties of SWE measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The results presented in this research strongly depend on the proper representation of snow cover processes by the model. This (Schmucki et al, 2014;Wever, Jonas, et al, 2014), focussing on the water transport scheme within the model (Wever et al, 2015;Würzer et al, 2017), and by distributed simulations using MeteoIO (Lehning et al, 2006;Schlögl, Marty, Bavay, & Lehning, 2016;Wever et al, 2017). Schlögl et al (2016) conducted a sensitivity analysis to systematically investigate the impact of different model setups on the robustness of modelled SWE and found that the input uncertainties of distributed simulations are in the same range as uncertainties of SWE measurements.…”
Section: Results In the Context Of Hydrological Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictors were selected based on physical intuition, inspection of the relevant literature and initial exploratory data analysis. Prior studies that were particularly helpful in this regard were Gurrapu et al (2016), who examined the influence of the PDO on streamflow in western Canada, Jenicek et al (2016), who examined the influence of snow accumulation and other variables on summer low flows, Coles et al (2017), who studied snowmeltrunoff generation on Canadian prairie hillslopes, and Wever et al (2017), who conducted model simulations of the joint effect of snowmelt and soil moisture on streamflow in a Swiss Alpine catchment. The predictor variables chosen are listed in Table 2.…”
Section: Selection Of Predictors and Analysis Methodsmentioning
confidence: 99%